Pyruvate–GPR31 axis induces LysoDC dendrite protrusion to M-cell pockets for effective immune responses - Katsuhiro Nakanishi; Takayuki Ajiro; Kaito Yukishima; Yuki Tsukamoto; Junichi Kikuta; Shinichiro Sawa; Michio Tomura; Nozomi Kinoshita; Wataru Shimanuki; Akio Suzuki; Shun Arai; Kazuki Maeshima; et al. (Gut Microbes)
Peyer’s patches (PPs) are sites of antigen entry and immunoinduction in the small intestine. In PPs, pathogens are transferred through microfold (M) cells; however, the mechanisms of antigen capture by mononuclear phagocytes beneath M cells remain unclear. Here, we demonstrate that bacterial metabolite pyruvate acted on lysozyme-expressing dendritic cells (LysoDCs), a monocyte-derived phagocyte subset, and induced protrusion of dendrites particularly with “balloon” shapes into basolateral M-cell pockets via its receptor, G-protein coupled receptor 31 (GPR31). Pyruvate administration in wild-type but not Gpr31b-deficient mice increased LysoDC uptake of orally infected Listeria monocytogenes. GPR31 signaling boosted antigen processing and altered gene expression. It also increased LysoDC migration to the interfollicular region, thereby promoting production of pathogen-specific Th1 cells as well as cytotoxic T cells, and effector T cell migration to the lamina propria. Furthermore, oral pyruvate administration conferred high resistance to a virulent L. monocytogenes strain in a GPR31-dependent manner. Collectively, the pyruvate – GPR31 axis plays critical roles in orchestrating intestinal protective immunity.